Modelo administrativo de la comercialización de yuca (Manihot esculenta crants) troceada para las MIPYMES - Párraga Bazurto, Luis Cayetano (2012)
This research was conducted between the months of October 2011 March 2012 in the districts of Northern Province Manabí (Tosagua, Junín, Chone, and Bolívar) in order to design an administrative model for the commercialization of yucca chopped in MSMES. The main objective of this research was to establish administrative and accounting system for chopped yucca commercialization and establish the beneficial cost. The achievement was the designing of the blueprint for the administration of the MSMES. The surveys conducted resulted in 100%. The example does not have any kind of system or administrative module. However, the need of an accounting administrative system was also 100%. This also shows that the existence of these exporting companies surpasses the ten years mark, province compared to the existence of exporting firms with over 20 years in this business. From the economic point the marketing of yucca for both entrepreneurs and exporters in profitable and sustainable.